Impact of different nutrient management strategies on growth, yield components and yield of coloured cotton (Gossypium hirsutum L.) cv. Vaidehi 1 - Selvakumar, Selvaraj; Ragavan, Thiruvengadam; Gurusamy, Arumugam; Prabhaharan, James; Gunasekaran, Mahalingam; Sivakumar, Thangasamy; Subramanian, Elangovan; Rani, Suramani; Arthirani, Bangaru; Sathishkumar, Arumugam; Hussainy, Syed Abul Hassan (Frontiers in Sustainable Food Systems, 2025)
Cotton (Gossypium spp.), often referred to as “white gold” and “the king of fibers”, is a major commercial fiber crop cultivated across various agroclimatic conditions, primarily used in the textile industry to manufacture fabrics. However, conventional white cotton production is associated with several environmental challenges including excessive water consumption, reliance on synthetic chemicals and the use of synthetic dyes, which contribute to soil degradation, water pollution and health hazards for farmers. In contrast, organic coloured cotton presents a sustainable alternative by naturally producing coloured fibres without the need for synthetic dyes. Additionally, it enhances soil fertility, conserves water and minimizes chemical inputs, providing ecological benefits while supporting the well-being of farming communities. The field experiments were carried out at the Central Farm, Agricultural College and Research Institute, TNAU, Madurai, Tamil Nadu, during the Kharif 2023 and Summer 2024 seasons. The present study aimed to evaluate the impacts of various nutrient management practices on the growth characteristics, yield attributes and yield of coloured cotton (Gossypium hirsutum L.) cv. Vaidehi 1. The experiment was designed using a randomized block design with nine treatments based on N-equivalence using different organic manures compared to inorganic fertilizers and replicated three times. The results indicated a significant increase in the growth characters (plant height, number of vegetative branches plant−1 and number of fruiting branches plant−1), yield attributes (number of fruiting points plant−1, number of bolls plant−1, number of bolls m−2, boll setting % and boll weight) and yield (seed cotton yield, lint cotton yield, stalk yield and biological yield) of coloured cotton with the application of 100% NPK applied through site-specific recommendation (T2), which was statistically on par with 100% NPK through blanket recommendation (T1). These were followed by the organic treatments like complete organic package (T9), cover crop with vermicompost (T4), cover crop with poultry manure (T5) and all other organic treatments during both seasons. No significant variations were recorded in the first fruiting node, length of fruiting branches as well as harvest index and lint percentage across the different nutrient management strategies.